Oxygen isotope analysis of bacterial and fungal manganese oxidation. Issue 4 (25th April 2018) - Sutherland, K. M.; Wankel, S. D.; Hansel, C. M.
Abstract: The ability of micro‐organisms to oxidize manganese (Mn) from Mn(II) to Mn(III/IV) oxides transcends boundaries of biological clade or domain. Many bacteria and fungi oxidize Mn(II) to Mn(III/IV) oxides directly through enzymatic activity or indirectly through the production of reactive oxygen species. Here, we determine the oxygen isotope fractionation factors associated with Mn(II) oxidation via various biotic (bacteria and fungi) and abiotic Mn(II) reaction pathways. As oxygen in Mn(III/IV) oxides may be derived from precursor water and molecular oxygen, we use a twofold approach to determine the isotope fractionation with respect to each oxygen source. Using both 18 O‐labeled water and closed‐system Rayleigh distillation approaches, we constrain the kinetic isotope fractionation factors associated with O atom incorporation during Mn(II) oxidation to −17.3‰ to −25.9‰ for O2 and −1.9‰ to +1.8‰ for water. Results demonstrate that stable oxygen isotopes of Mn(III/IV) oxides have potential to distinguish between two main classes of biotic Mn(II) oxidation: direct enzymatic oxidation in which O2 is the oxidant and indirect enzymatic oxidation in which superoxide is the oxidant. The fraction of Mn(III/IV) oxide‐associated oxygen derived from water varies significantly (38%–62%) among these bio‐oxides with only weak relationship to Mn oxidation state, suggesting Mn(III) disproportionation may account for differences in the fraction of mineral‐bound oxygen from water and O2 . Additionally, direct incorporation of molecular O2 suggests that Mn(III/IV) oxides contain a yet untapped proxy of δ 18 O O 2 of environmental O2, a parameter reflecting the integrated influence of global respiration, photorespiration, and several other biogeochemical reactions of global significance.